PROFESSIONAL RECOGNITION AND AWARDS AS INDICATORS OF EXCELLENCE IN COMMERCIAL PERFORMANCE - Cristina Constantino da Costa Silva, Amanda (Humanas em Perspectiva, 2025)
This article explores the intersection between professional recognition, award systems, and the measurement of commercial performance. The main objective is to discuss how the metrics used in award programs not only quantify sales success but also serve as a direct reflection of the management practices and leadership styles predominant in an organization. The adopted methodology consists of a systematic literature review, analyzing motivation theories, such as those by Maslow and Herzberg, and empirical studies on the impact of recognition on employee performance. The analysis demonstrates that while well-structured recognition programs can boost intrinsic and extrinsic motivation, increase talent retention, and foster a high-performance culture, the choice of Key Performance Indicators (KPIs) for these awards reveals the strategic priorities and values of the leadership. It is concluded that awards, when aligned with a holistic management vision and transformational leadership, transcend the function of a simple reward, becoming strategic tools for competence development, reinforcement of organizational culture, and the pursuit of sustainable commercial excellence. The study offers insights for managers on how to design recognition systems that are fair, motivating, and truly indicative of excellent performance.